2021
DOI: 10.1093/ckj/sfab168
|View full text |Cite
|
Sign up to set email alerts
|

The burden of subclinical cardiovascular disease in children and young adults with chronic kidney disease and on dialysis

Abstract: Introduction Cardiovascular disease (CVD) is a common cause of morbidity and mortality even in young people with chronic kidney disease (CKD). We examined structural and functional cardiovascular changes in patients with CKD stages 4-5 and on dialysis under 30 years of age. Methods 79 children and 21 young adults underwent cardiac CT for coronary artery calcification (CAC), ultrasound for carotid intima media thickness (cIMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Demographics of the study population (that completed follow-up, n = 57) at baseline are shown in Table 1 . The baseline characteristics of the whole cohort ( N = 100) and their bone and vascular measures have been published 11 , 12 and are summarized in Supplementary Tables S1 and S2 . Fifty-seven patients were followed up after a median of 1.45 (1.25, 1.81) years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographics of the study population (that completed follow-up, n = 57) at baseline are shown in Table 1 . The baseline characteristics of the whole cohort ( N = 100) and their bone and vascular measures have been published 11 , 12 and are summarized in Supplementary Tables S1 and S2 . Fifty-seven patients were followed up after a median of 1.45 (1.25, 1.81) years.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 100 children and young adults with CKD entered the study, and 57 were followed up after a median of 1.45 (1.25, 1.81) years. Cross-sectional data on bone health 11 and subclinical cardiovascular disease 12 in this cohort have been published ( N = 100). All further analyses described pertain to the 57 participants who were followed up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lalayiannis et al present in this issue of Clinical Kidney Journal significant evidence of subclinical cardiovascular disease in a young renal failure cohort [ 4 ]. The findings are based on thorough cardiovascular examination of 100 young kidney failure patients (chronic kidney disease stages 4 and 5) including patients on dialysis.…”
mentioning
confidence: 99%